Implementasi Augmented Reality untuk Pembelajaran Gerakan Pencak Silat Menggunakan Unity dan Vuforia - Fahmi; Alders Paliling; Ery Muchyar Hasiri; LM. Fajar Israwan (Ikatan Ahli Informatika Indonesia, 2024)
Pencak Silat is a traditional martial art that originated in Indonesia, now pencak silat is a sport that has many enthusiasts in various countries. At the State Junior High School 4 Wangi - Wangi, pencak silat still uses a learning method with direct practice in the field which is only done 1 time a week. This research aims to design and build a learning application for the Pencak Silat movement by applying Augmented Reality technology. In making this application, there are several stages, namely, character design and animation using avatars sdk and blender which then markers are stored in the Vuforia database and built using unity. This research produces the application of Augmented Reality in Learning Pencak Silat movements as a learning medium that can be used as a learning medium for students, where students can learn Pencak Silat movements by looking at the movements of characters in the application in 3 dimensions so that it will make students enthusiastic in learning Pencak Silat.